Microencapsulation of red grape juice by freeze drying and application in jelly formulation - Mihalcea, Liliana (Array, 2020)
The aim of this work is to obtain new food products enriched with bioactive compounds from concentrated grape juice microencapsulated by freeze drying using a whey protein isolate- chitosan system. The obtained powder showed an encapsulation efficiency of (86.1±4.0) %, with an anthocyanin mass fraction (expressed as cyanidin-3-O-glucoside equivalent) of (1.4±0.2) mg/g, while the total polyphenolic (expressed as gallic acid equivalents) and flavonoid (expressed as catechin equivalents) mass fractions were (3.3±0.6) and (1.6±0.5) mg/g, respectively. The confocal laser microscopy revealed the presence of the flavonoid pigments wrapped inside the matrix, whereas the anthocyanins were grouped into large and compact clusters. The microencapsulated powder was used for jelly formulation. The new food formulations have a satisfactory anthocyanin mass fraction ranging from (0.03±0.01) to (0.12±0.02) mg/g, while no significant differences were observed in flavonoid content. All the value-added jelly showed appreciable antioxidant activity. The in vitro digestibility results confirm a slow release of anthocyanins from the food matrices during simulated gastric digestion and a significant release of the bioactive compounds into the gut. The addition of microencapsulated powder caused a significant decrease in firmness, cohesiveness and springiness, leading to the destabilization of the gel structure, while reducing the attraction forces between the matrix components. The sensorial analysis indicated that the panellists preferred the sample with grape juice the most.